Evaluation of as‐extruded ternary Zn–Mg–Zr alloys for biomedical implantation material: In vitro and in vivo behavior. Issue 6 (2nd January 2019) - Ren, Tiantian; Gao, Xue; Xu, Cheng; Yang, Lijing; Guo, Pushan; Liu, Huinan; Chen, Yanxia; Sun, Wensheng; Song, Zhenlun
Abstract : In this study, Zn‐xMg‐0.5Zr alloys ( x  = 0.5, 1, 1.5 wt%) were designed to improve the mechanical properties and biodegradability of pure Zn for potential biomedical implantation materials. The microstructure, mechanical properties, in vitro corrosion behavior, and in vivo biocompatibility of the as‐extruded alloys were investigated. The Zn–Mg–Zr alloys exhibit a significant grain refinement and improved tensile strength, corrosion resistance, and cytotoxicity by comparison with pure Zn. With the increasing Mg content, the tensile strength and corrosion rate of Zn–Mg–Zr alloys increase whereas the elongation increases and then decreases and the cytocompatibility decreases. Due to the combination of hot extrusion and micro‐alloying of Mg and Zr, the Zn–1Mg–0.5Zr alloy has homogenous microstructure, uniform and slow biodegradation, improved mechanical properties and good biocompatibility, is a suitable candidate material for load‐bearing biodegradable implant application. Abstract : In this study, Zn–xMg–0.5Zr alloys ( x  = 0.5, 1, 1.5 wt%) were designed to improve the mechanical properties and biodegradability of pure Zn for potential biomedical implantation materials. The Zn–Mg–Zr alloys exhibit a significant grain refinement and improved tensile strength, corrosion resistance, and cytotoxicity by comparison with pure Zn.